Reflective journal as a solution for emotional regulation to anti-momster “Mama Monster” - Ninuk Dwi Puspa Handayani; Nihayatul Faizah; Maulydia Dwi Astuti; Emamiridya Erine Yupi; Eny Purwandari (Universitas Muhammadiyah Magelang, 2024)
Several cases of violence against children are increasingly mushrooming. This phenomenon is suspected to be a failure for parents to regulate the emotions they feel, especially negative emotions that often appear in everyday life. This community service is carried out with the aim of providing understanding to parents regarding the importance of regulating the emotions they feel through reflective journals. This activity is a psychoeducational seminar and reflective journal training as a solution to regulate emotions appropriately. This community service was carried out for parents at KB/TK Alam Muhammadiyah Surya Mentari Surakarta. The result of this service activity is that parents realize that anger is a natural reaction from the body that does not need to be avoided and must be transformed into appropriate behavior. Apart from that, indirectly reflective journals also become a conversation partner for parents in dealing with various emotions felt in everyday life. This community service has an impact on participants, namely parents, in terms of increasing knowledge about emotions and how to regulate them appropriately.